Long‐term stable 60 GHz optical two‐tone signal by destructive optical interference obtained from RF phase adjustment. Issue 9 (4th April 2016) - Chiba, A.; Akamatsu, Y.; Takada, K.
Abstract : An optical two‐tone signal with 60 GHz frequency spacing is experimentally demonstrated, by sinusoidally modulating two lightwaves with different modulation indices and RF phases. By superposing two modulation lightwaves with orthogonal polarisation, polarisation orthogonality is achieved between undesired low‐order optical sidebands and the desired high‐order optical sidebands together with the incident light‐wave. This enables us to suppress the undesired sidebands using polarisers instead of optical filter. Such operation has been implemented using optical modulator possessing RF ports for external termination, which is nested in one mode of polarisation‐maintaining Sagnac interferometer (PMSI). This implementation is equivalent to optical single‐sideband modulator, but required nested Mach–Zehnder structure is just one. Owing to this reduction together with use of one mode in PMSI, long‐term stable operation more than 6 h has been successfully obtained, with 29 dB suppression ratio of undesired first‐order sidebands against desired third‐order optical sidebands.